ESTABILIDADE GENÔMICA EM TRITICALE: RELAÇÃO ENTRE COMPORTAMENTO MEIÓTICO E ANORMALIDADES MITÓTICAS - Giacomin, Renata Mussoi (2014)
Triticale (X Triticosecale Wittimarck ) is an intergeneric hybrid derived from a cross between wheat and rye. It is widely used as food energy in animal feed and for making breads and biscuits. Triticale can present chromosome number n = 42 (hexaploid) or n = 56 (octaploides). Being a newly created allopolyploid, it may present instabilities during the meiotic process, which may result in loss of fertility. Cytogenetic analysis of meiotic behaviour, pollen fertility and genomic stability are important tools used to assist plant breeding programs to select stable genotypes. The objective of this study was to analyze the cytogenetic of triticale genotypes belonging to four generations P1, P2, F1, F2, RC1 and RC2, developed in the Genetic Improvement Program of Embrapa Trigo. The genotypes were cultivated in the experimental station of the Universidade Estadual do Centro Oeste, Brazil. For the cytogenetic analysis of meiotic behaviour, spikelets were collected during an early stage of development. The collected material was fixed in Carnoy and kept in 70% alcohol. Slides were prepared by crushing and staining spikelets with 1 % propionic carmine and analyzed by optical microscopy. 100 cells from each stage of meiosis were analyzed, obtained from six plants of each genotype. The meiotic index was calculated using the following formula: number of normal tetrads/total number of tetrads x 100. To analyze pollen viability the same technique was used, but with 1 % acetic carmine dye. GISH analyses were performed according to the pattern found in the literature using genomic DNA as a probe of rye and wheat as blocking. In general all genotypes presented instability during meiosis, with variation within genotypes. The backcrosses RC1 and RC2 showed the lowest average of abnormalities in meiotic stages and the largest meiotic index demonstrating high stability. The most common chromosome abnormalities were early rise chromosome, laggard chromosome, adhesions and bridges, and the presence of micronuclei. It was also shown a high rate of pollen viability in all analyzed genotypes, which means that the instability during meiosis is not affecting the fertility of plants analyzed. Through GISH analysis, it was identified the presence of a chromosomal translocation in one of the genotypes analyzed: Embrapa 53. However further investigations on the possibility of this translocation be interfering in the cultivar genomic stability are suggested.